A Clinicodemographic Study of Indian Patients with Hidradenitis Suppurativa and its Association with Metabolic Syndrome - Dipankar De; Narayanan Baskaran; Vishal Thakur; Vinod H. Hanumanthu; Shirin Bakshi; Sudhir Bhandari; Deeksha Katoch; Sanjeev Handa (Wolters Kluwer Medknow Publications, 2024)
Background: Hidradenitis suppurativa (HS) is a chronic inflammatory disorder affecting pilosebaceous units causing painful nodules, abscesses, and scarring. Despite global studies linking HS to metabolic syndrome, insights specific to Indian patients are limited. Materials and Methods: This study aimed to describe the clinicodemographic characteristics and study frequency of metabolic syndrome in Indian HS patients. In this cross-sectional study, 100 HS patients were evaluated for clinical characteristics, comorbidities, pain and suppuration scores, quality of life, and ophthalmological and dental abnormalities. Metabolic parameters, including anthropometry and blood markers, were performed in all cases and 100 age- and gender-matched controls. Results: The mean age was 29.47 years, with a male predominance of 57%. HS predominantly affected a combination of two or more sites (60%), with nodules as primary lesions (95%). Quality of life was significantly impaired, with 49% experiencing moderate impact as per Dermatology Life Quality Index. Metabolic derangements, represented by an increased body mass index, waist circumference, blood pressure, fasting blood sugar, and fasting insulin, were significantly more frequent in HS cases compared to controls (P < 0.001). The frequency of metabolic syndrome in HS patients was 42%, significantly higher than controls (8%, P < 0.001) with a relative risk of 5.25 (95% CI 2.68-10.58). Dental and ophthalmological abnormalities were observed in 35% and 21.7% of screened patients, respectively. Limitations: Cross-sectional nature, no prospective assessment to determine evolution with time, and limited patient number are the limitations of the study. Conclusion: A substantial association with metabolic syndrome and considerable impact on quality of life is seen in Indian HS patients, emphasizing the need for metabolic screening and holistic management strategies.